Pengembangan Gim Edukasi Pengenalan Patung di DKI Jakarta Berbasis Desktop - Erick Richardo; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop a game to give players insight into the statues in DKI Jakarta, so that players can understand the history of these statues. The statues include: Diponegoro Statue, General Sudirman Statue, Moh. Husni Thamrin, Ismail Marzuki Statue, Chairil Anwar Statue, Small Gus Dur Statue, General Ahmad Yani Statue, DR. GSSJ Ratulangi, Hero Statue, Archer Statue, Statue of the Great General A.H. Nasution, Statue of Bung Karno. The method used in making this game is Game Development Life Cycle (GDLC). In the GDLC method, there are several stages, including: Initiation, Pre-production, Production, Testing, Beta, and Release. The result of this research is an educational game "Belajar mengenal Patung di DKI Jakarta". The game development uses a game engine called Construct 2. In this game, there are four displays that players will see, including: Main Menu, Quiz, Learning Sculpture, and How to play.From the beta test results, 9 out of 16 people understand the statue better after playing the game.